The folk : music, modernity, and the political imagination - Cole, Ross (University of California Press, 2021)
"Who were 'the folk'? This question has haunted generations of radicals and reactionaries alike. The Folk traces the musical culture of these elusive figures in Britain and the US during a crucial period from 1870 to 1930, and beyond to the contemporary alt-right. It follows an insistent set of disputes surrounding the practice of collecting, ideas of racial belonging, the poetics of nostalgia, and the pre-history of European fascism. It is the biography of a people who exist only as a symptom of the modern imagination and the archaeology of a landscape directing the flow of global politics today"--